Determination of Oil and Grease in Produced Water and their Effects on Surrounding Soils - Said Akbar Khan; Ayesha Hafeez (International Journal of Economic and Environmental Geology, 2018)
This study was conducted to determine the concentrations of oil and grease in produced water from Sadqal oil and gas field in Fateh Jang, Punjab, Pakistan and their impact on surrounding soil. Produced water samples were collected from various locations including inlet of pond A, pond A, inlet of pond B, pond B, outlet of pond B and external stream. Concentration of oil and grease from various locations showed that all values were higher than the permissible limit of Pakistan Environmental Protection Agency (Pak-EPA). Soil samples were collected from the same location points of the produced water. In soil samples oil and grease were found in high amounts due to continuous discharge of produced water in that area. Therefore, produced water should be treated properly before being released into the surrounding environment and Pak-EPA should have regular monitoring programs.